Controlled‐release urea decreased ammonia volatilization and increased nitrogen use efficiency of cotton. Issue 6 (4th September 2017) - Tian, Xiaofei; Geng, Jibiao; Guo, Yanle; Li, Chengliang; Zhang, Min; Chen, Jianqiu
Abstract: Excessive nitrogen (N) fertilizer input leads to higher N loss via ammonia (NH3 ) volatilization. Controlled‐release urea (CRU) was expected to reduce emission losses of N. An incubation and a plant growth experiment with Gossypium hirsutum L. were conducted with urea and CRU (a fertilizer mixture of polymer‐coating sulfur‐coated urea and polymer‐coated urea with N ratios of 5 : 5) under six levels of N fertilization rates, which were 0% (0 mg N kg −1 soil), 50% (110 mg N kg −1 soil), 75% (165 mg N kg −1 soil), 100% (220 mg N kg −1 soil), 125% (275 mg N kg −1 soil), and 150% (330 mg N kg −1 soil) of the recommended N fertilizer rate. For each type of N fertilizer, the NH3 volatilization, cotton yield, and N uptake increased with the rate of N application, while N use efficiency reached a threshold and decreased when N application rates of urea and CRU exceeded 238.7 and 209.3 mg N kg −1 soil, respectively. Ammonia volatilization was reduced by 65–105% with CRU in comparison to urea treatments. The N release characteristic of CRU corresponded well to the N requirements of cotton growth. Soil inorganic N contents, leaf SPAD values, and net photosynthetic rates were increased by CRU application, particularly from the full bloom stage to the initial boll‐opening stage. As a result, CRU treatments achieved significantly higher lint yield by 7–30%, and the N use efficiency of CRU treatments was increased by 25–124% relative to that of urea treatments. These results suggest that the application of CRU could be widely used for cotton production with higher N use efficiency and lower NH3 volatilization.